Clinical management of acute otitis externa concurrent with auricular myiasis in a doe - Abdullah, Faez Firdaus Jesse; Lim, Eric Teik Chung; Bitrus, Asinamai Athliamai; Peter, Innocent Damudu; Hambali, Idris Umar (Premier Publishers, 2018)
This case report described the clinical management of otitis externa concurrent with myiasis in a doe. Briefly, intravenous fluid therapy was instituted and the infected wound was thoroughly washed with a diluted hydrogen peroxide and a combination of diluted hibiscrub, diluted iodine, acriflavin and beavate. Topederm® was applied topically for one week. Non-steroidal anti-inflammatory drug (NSAID) Flunixin meglumine (2.2 mg/kg, IV was administered once daily for three days to reduce inflammatory reaction and Ivermectin (1 mL/50kg) was given subcutaneously once. The prognosis was good and there was improvement in the wound healing and the overall condition of the animal one week after treatment. The farmer was advised to ensure the practice of good management hygiene and also employ the use of insect repellents in and around the farm.